Museums in China : the politics of representation after Mao - Varutti, Marzia (Heritage matters series, 2014)
Museums in China have undergone tremendous transformations since they first appeared in the country in the late nineteenth century. Futuristic, state-of-the-art museums have today become symbols of China's global cultural, economic and technological prominence, and over the last two decades, the number of Chinese museums has increased at an unprecedented rate, with China set to become the country with the highest number of museums in the world. But why have museums become so important? This book, based on extensive research in a number of the museums themselves, examines recent changes in their display methods, narratives, actors and architectural style. It also considers their representations of Chinese national identity, millenarian history and extraordinary cultural diversity.